2016
DOI: 10.1007/s13402-016-0286-4
|View full text |Cite
|
Sign up to set email alerts
|

MGMT DNA repair gene promoter/enhancer haplotypes alter transcription factor binding and gene expression

Abstract: The data generated support our hypothesis that promoter haplotypes alter the binding of TFs to the MGMT P/E and, subsequently, affect their regulatory function on MGMT promoter activity and expression level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…A case in point is the G-1157aA, which when found in haplotype 30, it produced a significant decrease in promoter activity, however, when G-1157aA is found alone (haplotype M4), the activity was significantly increased, indicating that single SNPs are not always the phenotype drivers. This corroborates our earlier observations involving the O-6-methylguanine DNA methyltransferase (MGMT) gene [20,21]. In these studies, we found the MGMT promoter SNP C575A (rs113813075) may have no effect in one haplotype but can have dramatic effects on MGMT expression when found in another haplotype.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A case in point is the G-1157aA, which when found in haplotype 30, it produced a significant decrease in promoter activity, however, when G-1157aA is found alone (haplotype M4), the activity was significantly increased, indicating that single SNPs are not always the phenotype drivers. This corroborates our earlier observations involving the O-6-methylguanine DNA methyltransferase (MGMT) gene [20,21]. In these studies, we found the MGMT promoter SNP C575A (rs113813075) may have no effect in one haplotype but can have dramatic effects on MGMT expression when found in another haplotype.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, the G-240A variant could generate a higher affinity binding site for a transcription activator or alter the secondary structure of the DNA. Additional support to this hypothesis is provided by our previous work with MGMT [20,21]. In these studies, we observed haplotype-dependent TF binding profiles that significantly correlated with MGMT promoter activity [21].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We can take advantage here from our work, which could be a potential target that can help overcome the unmethylated patients’ resistance to TMZ. Interestingly, Xu et al [ 23 ] recently found that haplotype has an impact on transcription factor binding in the MGMT promoter/enhancer region consequently regulating MGMT expression. This finding may help our work on Gli1 to fit better on evaluating MGMT activity.…”
Section: Discussionmentioning
confidence: 99%
“…RLU, relative light units; siRNA, small interfering RNA. Color images available online at www.liebertpub.com/dna with recent data from our laboratory that indicated that different haplotypes alter the binding of TFs to the MGMT promoter and, subsequently, affect its promoter activity and expression level (Xu et al, 2016). The siRNA studies with haplotype 30, which has very low basal promoter activity, revealed that none of the tested siRNAs had any effect on its activity (Fig.…”
Section: Figmentioning
confidence: 62%